In: Math
( NO HAND WRITING PLEASE )
Q1: Suppose that a and b are integers, a ≡ 11 (mod 19), and
b ≡ 3 (mod 19). Find the integer c with 0 ≤ c ≤ 18 such
that
a) c ≡ 13a (mod 19).
b) c ≡ 8b (mod 19).
c) c ≡ a − b (mod 19).
d) c ≡ 7a + 3b (mod 19).
e) c ≡ 2a2 + 3b2 (mod 19).
Q2:
List all the steps used to search for 10 in the sequence 1,3, 4, 5, 6, 8, 9, 11 using
a) A linear search.
b) A binary search.
1) Given that a and b are integers such that a 11(mod 19)
and b
3(mod 19) and c
is an integer such that
.
Now, a) We have, a 11(mod 19)
i.e., a = 19*m + 11, where m is an integer.
i.e., 13a = 13*(19*m + 11)
i.e., 13a = 19*(13*m) + 143
i.e., 13a = 19*(13*m + 7) + 10
i.e., 13a = 19*m' + 10 [where m' = 13*m + 7]
Given, c 13a(mod 19)
i.e., c = 19*k + 13a, where k is an integer
i.e., c = 19*k + 19*m' + 10
i.e., c = 19*(k + m') + 10 [where m' = 13*m + 7]
i.e., c = 19*k' + 10 [where k' = k + m']
Since, c is an integer such that
and k' is an integer.
Therefore, c = 10 [putting k' = 0]
b) We have, b 3(mod 19)
i.e., b = 19*n + 3
i.e., 8b = 8*(19*n + 3)
i.e., 8b = 19*(8*n) + 24
i.e., 8b = 19*(8*n + 1) + 5
Given, c 8b(mod 19)
i.e., c = 19*k + 8b, where k is an integer
i.e., c = 19*k + 19*(8*n + 1) + 5
i.e., c = 19*(k + 8*n + 1) + 5
i.e., c = 19*k' + 5 [where k' = k + 8*n + 1]
Since, c is an integer such that
and k' is an integer.
Therefore, c = 5 [putting k' = 0]
c)We have, c a-b(mod 19)
i.e., c = 19*k + (19*m + 11) + (19*n + 3)
i.e., c = 19*(k+m+n) + 14
i.e., c = 19*k' + 14 [where k' = k+m+n]
Since, c is an integer such that
and k' is an integer.
Therefore, c = 14 [putting k' = 0]
d) We have, c 7a+3b(mod
19)
i.e., c = 19*k + 7*(19*m + 11) + 3*(19*n + 3)
i.e., c = 19*k + 19*(7*m + 3*n) + 77 + 9
i.e., c = 19*(k + 7*m + 3*n) + 86
i.e., c = 19*(k + 7*m + 3*n + 4) + 10
i.e., c = 19*k' + 10 [where k' = k + 7*m + 3*n + 4]
Since, c is an integer such that
and k' is an integer.
Therefore, c = 10 [putting k' = 0]
e) We have, c
2a2+3b2(mod 19)
i.e., c = 19*k + 2*(19*m + 11)2 + 3*(19*n + 3)2
i.e., c = 19*k + 2*[19*(19*m2 + 22*m) + 121] + 3*[19*(19*n2 + 6*n) + 9]
i.e., c = 19*[k + 2*(19*m2 + 22*m) + 3*(19*n2 + 6*n)] + 242 + 27
i.e., c = 19*[k + 2*(19*m2 + 22*m) + 3*(19*n2 + 6*n)] + 269
i.e., c = 19*[k + 2*(19*m2 + 22*m) + 3*(19*n2 + 6*n) + 14] + 3
i.e., c = 19*k' + 3 [where k' = k + 2*(19*m2 + 22*m) + 3*(19*n2 + 6*n) + 14]
Since, c is an integer such that
and k' is an integer.
Therefore, c = 3 [putting k' = 0]